Analysis of Standard Operational Procedure Hotel Using AHP to Get the Best Ranking Order - Julio Warmansyah (Sekolah Tinggi Ilmu Komputer Binaniaga, 2021)
Standard Operating procedure accounting system, controlling model management of hotel administration credit approval to facilitate the supervision of companies that will apply for credit. Credit meetings to be able to control the account provided by the credit facility. Direct meeting to ensure that all booking or activities that result in billing are billed directly to avoid. Credit card procedure to make sure the financial controller is responsible for developing a system and following procedures are placed. Foreign currency loss/gain, not front office to make sure all profit and loss associated with foreign exchange transaction must be reflected in profit and loss account unless the management contract states otherwise. Collection to make a sure timeline of billing accuracy of data and effective method and follow up. Use the collection agencies/attorney to ensure the issuing billing is carried out the control so that there are no arrears. Collection letters to maintain a highly professional business image through consistent verbal and written collection efforts. Accounts receivable balancing to ensure the accuracy of the records and can avoid billing errors and causes of loss of revenue. Payment receivable to avoid data error regard payment made posting to city ledger establish debt bad provision to maintain provision for bad debt to cover.